2018
DOI: 10.1371/journal.pone.0189634
|View full text |Cite
|
Sign up to set email alerts
|

Response monitoring of breast cancer patients receiving neoadjuvant chemotherapy using quantitative ultrasound, texture, and molecular features

Abstract: BackgroundPathological response of breast cancer to chemotherapy is a prognostic indicator for long-term disease free and overall survival. Responses of locally advanced breast cancer in the neoadjuvant chemotherapy (NAC) settings are often variable, and the prediction of response is imperfect. The purpose of this study was to detect primary tumor responses early after the start of neoadjuvant chemotherapy using quantitative ultrasound (QUS), textural analysis and molecular features in patients with locally ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 41 publications
3
42
1
1
Order By: Relevance
“…This could potentially reduce the number of false-positive biopsies as well as the number of falsely down-staged lesions. Similarly to what has already been shown for US by Sannachi et al 50 and for SoS US by Lupinacci et al, 51 SoS-US could potentially be used as a fast and easy tool to predict the tumor response to chemotherapy. The current resolution is too low to make a conclusive statement on inner lesion structure.…”
Section: Discussionsupporting
confidence: 52%
“…This could potentially reduce the number of false-positive biopsies as well as the number of falsely down-staged lesions. Similarly to what has already been shown for US by Sannachi et al 50 and for SoS US by Lupinacci et al, 51 SoS-US could potentially be used as a fast and easy tool to predict the tumor response to chemotherapy. The current resolution is too low to make a conclusive statement on inner lesion structure.…”
Section: Discussionsupporting
confidence: 52%
“…In recent years, most studies used GLCM texture features for predicting the molecular subtypes of breast tumors or the pathological response to neoadjuvant chemotherapy (49,50). In this study, additional features were explored, such as histogram features, GRLM features, and DWT features, and the experimental results of univariate analysis demonstrated that those features were highly related to HER2 2+ expression status.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that BRCA patients with high variant burden in ABCC1 are less prone to respond appropriately to pharmacological therapy with MRP1 substrates. Thus, such at-risk individuals are likely to benefit from earlier and more frequent monitoring, ideally using more sensitive methods, such as magnetic resonance imaging 58 or quantitative ultrasound spectroscopy, 59,60 which can detect early events (tumor cell death) that precede changes in tumor size.…”
Section: Discussionmentioning
confidence: 99%